Utilization of rocks and ectomycorrhizal fungi to promote growth of eucalypt - Alves,Luciano (2010)
The utilization of rocks as fertilizers is limited by their low solubility. However, solubilization may be achieved by some micro-organisms, such as ectomycorrhizal fungi (ECMf). The aim of this study was to evaluate the potential of seven isolates of ECMf to solubilize two rocks, alkaline breccia and granite, and to liberate potassium and phosphorus for Eucalyptus dunnii seedlings under greenhouse conditions. Fungal inoculants were produced in a peat-vermiculite-liquid medium mixture and added to the planting substrate at 10 %. Rocks were ground up and added at 0.500 mg and 16.0 mg per plant, as a source of phosphorus and potassium, respectively. Other nutrients were added and E. dunnii seeds were sown. Control plants, non-inoculated, were fertilized with the same amount of phosphorus and potassium using soluble forms. After 90 days, the plant height, shoot dry weight, root length, phosphorus and potassium contents, and mycorrhizal colonization were evaluated. Alkaline breccia was more efficient than granite as a source of phosphorus and potassium for the plants, and may be an alternative to conventional fertilizers. Isolates UFSC-Pt22 (Pisolithus sp.) and UFSC-Pt186 (Pisolithus microcarpus) were the most efficient in promoting plant growth, mainly when combined with alkaline breccia to replace potassium and phosphorus fertilizers, respectively.